Sensitivity analysis on supersonic-boundary-layer stability subject to perturbation of flow parameters - Guo, Peixu; Gao, Zhenxun; Jiang, Chongwen; Lee, Chun-Hian (Physics of fluids (1994), 2021)
The compressible-boundary-layer stability can be considerably influenced by base flow distortion. The distortion may originate from perturbations of flow parameters, such as the Mach number. In this paper, sensitivities of the boundary layer stability to certain flow parameters are derived analytically by utilizing the homotopy analysis (with codes shared), in conjunction with a direct-adjoint stability theory. The sensitivities can be categorized according to the routes the distortion evolves. Route I is that parameters distort the base flow (Sensitivity A), which, in turn, affect the eigenvalue of the linear stability equation (Sensitivity B). Route II gives rise to the effects of flow parameters onto eigenvalues caused by direct perturbation of the linear operators (Sensitivity C). Results indicate that Sensitivity A is characterized by the only peak found on the sensitivity profile that corresponds to the maximum gradient of base flow; for Sensitivity B, production terms, e.g., the mean-shear terms, are found to be significant, while for Sensitivity C, which is rarely discussed in existing literature, the pressure gradient terms in the momentum equations are dominant in affecting the stability via route II. Furthermore, route II can be more significant than route I. Having examined the variation of the mean shear gradient, d ( ρ ¯ d u ¯ / d y ) / d y, near the critical layer yc, it is proven that the sensitivity of the eigenvalue to the velocity or temperature distortion is negative at yc under certain assumptions, particularly for the temperature-relevant sensitivity that has hardly been discussed before.